Alterations in Localized Electrical Impedance Myography of Biceps Brachii Muscles Paralyzed by Spinal Cord Injury - Li, Le; Stampas, Argyrios; Shin, Henry; Li, Xiaoyan; Zhou, Ping (Frontiers in Neurology, 2017)
This study assessed electrical impedance myography (EIM) changes after spinal cord injury (SCI) with a localized multi-frequency technology. The EIM measurement was performed on the biceps brachii muscle at rest condition of 22 cervical SCI, and 23 neurologically intact subjects as control group. The results showed that there was a significant decrease in muscle reactance (X) and phase (θ) at selected frequencies (i.e. 50 kHz and 100 kHz) in SCI compared to control. There was no significant difference in muscle resistance (R) between the two groups. The anisotropy examination revealed that SCI group had a decreased anisotropy ratio in resistance. In addition, the multi-frequency spectrum analysis showed a decreased slope of the resistance-logarithm frequency in SCI group when compared to healthy control. Findings of the EIM changes are related to inherit muscle changes after the injury. Since EIM requires no patient effort and is quick and convenient to conduct, it may provide a useful tool for examination of paralyzed muscle changes after SCI.